Pengembangan E-Book Teknik Gerak Dasar Atletik Siswa Kelas 5 Sd Negeri 39 Kota Lubuklinggau - Tri Juniarti; Ahmad Gawdy Prananosa; Wawan Syafutra (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2022)
This study aims to develop an E-book of basic athletic movement techniques for 5th-grade students of SD Negeri 39 Lubuklinggau City and to determine the quality of the E-book from the aspects of validity and practicality as having a potential effect. This research is development research that refers to developing a 4-D model. The instruments used to measure the quality of the developed E-book include validation sheets and practicality questionnaires with an average score of . The product of this research is an E-book of basic motion techniques for grade 5 elementary school athletics. The results showed that: (1) linguists were categorized as quite valid with a total of 0.64 media experts in the category "High enough, 0.67 in the category of "High enough" linguists, and material experts with a total of 0.74 categorized as "High Enough." (2) The practicality of the developed e-book was obtained from the teacher and student response questionnaire results (one-to-one and small-group tests). The individual test (one-to-one) results are categorized as practical with an average score of 3.2, and the results of the small group test are classified as quite practical with an average score of 3.1. In conclusion, from the results of the study, it can be concluded that the basic athletic movement technique e-book for students is categorized as valid and practical and has a potential effect for use on athletes Keywords: E-book , movement technique, of basic athletic